Contemporary Politikoi [Statesmen] and Other Sophists in Plato’s Political Dialogues (Revista Archai, 2025)
This paper argues that Plato in the Statesman consistently rejects all existing forms of constitution, separating off one, “the knowledgeable constitution,” from any other sort of rule, whether by a single individual, by a few, or by the many, and whether rule and the offices into which it is organized are or are not governed by effective checks and balances - a division that gives us kingship vs tyranny, aristocracy vs oligarchy, and two different types of democracy. All existing “statesmen” are written off without exception as “sophists” and “experts in faction,” and the quality of the laws of any existing constitution is declared to be at best sub judice insofar as they have all been formulated in the absence of the relevant political expertise. The paper goes on to consider these outcomes further, in relation to Plato’s Republic and Laws.